Description of the New Species Laccaria albifolia (Hydnangiaceae, Basidiomycota) and a Reassessment of Laccaria affinis Based on Morphological and Phylogenetic Analyses - Francesco Dovana; Roberto Para; Gabriel Moreno; Edoardo Scali; Matteo Garbelotto; Bernardo Ernesto Lechner; Luigi Forte (Journal of Fungi)
Laccaria is a diverse and widespread genus of ectomycorrhizal fungi that form symbiotic associations with various trees and shrubs, playing a significant role in forest ecosystems. Approximately 85 Laccaria species are formally recognised, but recent studies indicate this number may be an underestimation, highlighting the need for further taxonomic studies to improve our understanding of species boundaries. This manuscript focuses on Laccaria affinis, originally described by Singer in 1967 as Laccaria laccata var. affinis, and details a comprehensive study of its morphological and molecular characteristics, including the examination of its holotype and recent collections from Italy and the United Kingdom. Our findings reveal significant micromorphological traits that enhance the original description. Phylogenetic analyses indicate that L. affinis occupies a distinct clade within Northern Hemisphere Laccaria species, although minimal genetic differences challenge its independence from L. macrocystidiata. Consequently, we propose that these two taxa be considered synonymous. This study not only contributes to the understanding of Laccaria diversity but also proposes the formal designation of an epitype for L. affinis, thereby providing a foundation for future research on this ecologically significant genus. Furthermore, a new species named Laccaria albifolia belonging to the “/Laccaria bicolor complex clade” is described here on the base of six collections from Italy and Spain.